Impacts of hosting forced migrants in poor countries - Maystadt, Jean-François; Hirvonen, Kalle; Mabiso, Athur; Vandercasteelen, Joachim (Annual Reviews, 2019)
Most of the world's displaced people are hosted in low-income countries. Focusing on evidence from poor countries, we review the literature on the economic consequences of hosting refugees or internally displaced people. In the short run, violence, environmental degradation, and disease propagation are major risks to the host populations. In the long run, infrastructure, trade, and labor markets are key channels that determine the impacts on host communities. These impacts can be positive or negative and often unequally distributed among different hosts. We discuss policy options for building resilience in the light of this evidence. Investments in road infrastructure and deepening trade with refugees’ countries of origin are strategies worth exploring for enhancing resilience and transitioning from humanitarian assistance toward development. Finally, we identify key knowledge gaps in this literature and formulate a research agenda for the near future.